Prevalence and risk factors for diabetic peripheral neuropathy, neuropathic pain and foot ulceration in the Arabian Gulf region. Issue 9 (5th May 2022) - Ponirakis, Georgios; Elhadd, Tarik; Al Ozairi, Ebaa; Brema, Imad; Chinnaiyan, Subitha; Taghadom, Etab; Al Kandari, Jumana; Al Wotayan, Rehab; Al Ozairi, Abdulla; Aljohani, Naji; AlMistehi, Wael; Al Qahtani, Nora; et al.
Abstract: Aims/Introduction: This study determined the prevalence and risk factors for diabetic peripheral neuropathy (DPN), painful DPN and diabetic foot ulceration (DFU) in patients with type 2 diabetes in secondary healthcare in Qatar, Kuwait and the Kingdom of Saudi Arabia. Materials and Methods: Adults aged 18–85 years with type 2 diabetes were randomly enrolled from secondary healthcare, and underwent clinical and metabolic assessment. DPN was evaluated using vibration perception threshold and neuropathic symptoms and painful Diabetic Peripheral Neuropathy was evaluated using the Douleur Neuropathique 4 questionnaire. Results: A total of 3, 021 individuals were recruited between June 2017 and May 2019. The prevalence of DPN was 33.3%, of whom 52.2% were at risk of DFU and 53.6% were undiagnosed. The prevalence of painful DPN was 43.3%, of whom 54.3% were undiagnosed. DFU was present in 2.9%. The adjusted odds ratios for DPN and painful DPN were higher with increasing diabetes duration, obesity, poor glycemic control and hyperlipidemia, and lower with greater physical activity. The adjusted odds ratio for DFU was higher with the presence of DPN, severe loss of vibration perception, hypertension and vitamin D deficiency. Conclusions: This is the largest study to date from the Middle East showing a high prevalence of undiagnosed DPN, painful DPN and those at risk of DFU in patients with type 2 diabetes, and identifies their respective risk factors. Abstract : This is the largest prevalence study to date which has deployed standardized methodology in the Middle East to show a high prevalence of undiagnosed diabetic peripheral neuropathy (DPN), painful DPN and those at risk of diabetic foot ulceration (DFU). We have also identified obesity, poor glycemic control, hyperlipidemia, smoking cigarettes, and reduced physical activity as modifiable risk factors for DPN and severe loss of vibration perception, DPN, hypertension, and vitamin D deficiency as risk factors for DFU. These findings argue for a systematic approach to the diagnosis and management of risk factors for DPN.